An Unprecedented Kernel Growth Mode and Layer‐Number‐Odevity‐Dependent Properties in Gold Nanoclusters. Issue 2 (18th November 2019) - Liao, Lingwen; Wang, Chengming; Zhuang, Shengli; Yan, Nan; Zhao, Yan; Yang, Ying; Li, Jin; Deng, Haiteng; Wu, Zhikun
Abstract: Kernel atoms of Au nanoclusters are packed layer‐by‐layer along the [001] direction with every full (001) monolayer composed of 8 Au atoms (Au8 unit) in nanoclusters with formula of Au8n+4 (TBBT)4n+8 (n is the number of Au8 units; TBBTH=4‐tert‐butylbenzenelthiol). It is unclear whether the kernel atoms can be stacked in a defective‐layer way along the [001] direction during growth of the series of nanoclusters and how the kernel layer number affects properties. Now, a nanocluster is synthesized that is precisely characterized by mass spectrometry and single‐crystal X‐ray crystallography, revealing a layer stacking mode in which a half monolayer composed of 4 atoms (Au4 unit) is stacked on the full monolayer along the [001] direction. The size and the odevity of the kernel layer number influence the properties (polarity, photoluminescence) of gold nanoclusters. The obtained nanocluster extends the previous formula from Au8n+4 (TBBT)4n+8 to Au4n+4 (TBBT)2n+8 (n is the number of Au4 units). Abstract : The nanocluster Au56 (TBBT)34 was synthesized. X‐ray crystallography revealed a defective kernel layer stacking mode different from that shared by a magic series of nanoclusters, Au28 (TBBT)20, Au36 (TBBT)24, Au44 (TBBT)28, Au52 (TBBT)32, and Au56 (TBBT)34 . Not only the size but also the odevity of the kernel layer number influences both polarity and photoluminescence of the metal nanoclusters.